Environmental Activism of Islamic Organizations: Environmental Diplomacy Strategies in Facing the Global Climate Crisis - Dewi, Nevy Rusmarina (POLITEA, 2025)
This study examines the roles of Indonesia’s major Islamic organizations, Muhammadiyah and Nahdlatul Ulama (NU), in environmental diplomacy at both national and global levels through the lens of Green Islam. This research uses a field research method with a qualitative-descriptive approach.. The findings reveal that Green Islam rooted in the principles of tawhid, khalifah, and Amanah provides an ethical foundation for both organizations to develop environmental jurisprudence, ecological education, and public advocacy. Muhammadiyah demonstrates a rational-progressive approach through initiatives such as Fikih Air, Fikih Energi, Eco-Mosque programs, and the Green Ramadan campaign. Conversely, NU emphasizes a spiritual-contextual approach through Fikih Iklim, Green Pesantren, and the Santri Environmental Movement. Both organizations actively participate in international forums such as COP-26 to COP-28, collaborate with global institutions, and contribute to the Islamic Declaration on Global Climate Change. The study concludes that NU and Muhammadiyah function as significant non-state actors in Indonesia’s environmental diplomacy, combining religious values, education, and transnational networks, thereby strengthening Indonesia’s position as a promoter of ecological ethics in international relations.